2011
DOI: 10.1007/s00231-011-0924-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of thermal radiation on MHD slip flow over a flat plate with variable fluid properties

Abstract: The influence of partial slip, thermal radiation and temperature dependent fluid properties on the hydromagnetic fluid flow and heat transfer over a flat plate with convective surface heat flux at the boundary and nonuniform heat source/sink is studied. The transverse magnetic field is assumed as a function of the distance from the origin. Also it is assumed that the fluid viscosity and the thermal conductivity vary as an inverse function and linear function of temperature respectively. Using the similarity tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 41 publications
3
43
0
Order By: Relevance
“…The temperature of the sheet is , (9) where is the reference temperature, is the surface temperature and is the temperature of the fluid exterior the boundary layer. The wall surface concentration is given by the expression (10) is the wall surface concentration and is the concentration of the fluid outside the boundary layer.…”
Section: Basic Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…The temperature of the sheet is , (9) where is the reference temperature, is the surface temperature and is the temperature of the fluid exterior the boundary layer. The wall surface concentration is given by the expression (10) is the wall surface concentration and is the concentration of the fluid outside the boundary layer.…”
Section: Basic Equationmentioning
confidence: 99%
“…The effects of radiation on heat transfer problems have considered by Raptis [3], Makinde [4], Ibrahim et at [5], Hayat et at [6], Pal [7], Shit and Haldar [8]. In recent times Das [9] investigated the impact of thermal radiation on MHD slip flow over a flat plat with variable fluid properties.…”
Section: Introductionmentioning
confidence: 99%
“…parameter θ dimensionless temperature w axial velocity component u radial velocity component η similarity variable τ ratio of nanoparticle heat capacity to base fluid σ electrical conductivity υ kinematic viscosity α thermal diffusivity D B thermophoretic diffusion coefficient flow have been considered by many researchers [1,[3][4][5][6]8,17,23,27,49] due to its significance to most practical fluid flow situations. When flow system characteristics size is small or low flow pressure, the assumption of no slip boundary condition becomes insufficient and inadequate in predicting the flow behavior under such scenario.…”
Section: Nomenclaturementioning
confidence: 99%
“…In efforts to study fluid flow between parallel surfaces, Mustafa et al [25] investigated the heat and mass transfer between parallel plates undergoing unsteady squeezing fluid flow while Hayat et al [11] presented the squeezing flow of second grade fluid between parallel disk in the presence of magnetic field. In another work, Domairry and Aziz [3] applied the homotopy perturbation method to study the effect of suction and injection on MHD squeeze flow between parallel disks. The squeezing flow viscous fluid flow between plates under unsteady condition was analyzed by Siddiqui et al [47].…”
Section: Introductionmentioning
confidence: 99%
“…Cogley et al [13] showed that the fluid does not absorb its own emitted radiation in the optically thin limit but the fluid does absorb radiation emitted by the boundaries. The radiation effects on heat and mass transfer boundary layer flow have been studied by many authors [14][15][16]. Recently Abdul-Kahar et al [17] analyzed the boundary-layer flow of a nanofluid past a porous vertical stretching surface in the presence of chemical reaction with heat radiation using scaling group transformation.…”
Section: Introductionmentioning
confidence: 99%